Govor pri Sv. Trojici v Slovenskih goricah - Koletnik, Mihaela (Jezik in slovstvo, 2000)
The speech of Sv. Trojica belongs to the Eastern Slovenske gorice subdialect, and with it to the Panonic dialect group. The speech does not have tonemic oppositions, but it has preserved the quantitative opposition. The consonant system differs from that of standard Slovene only in a few individual developments. Accidence paradigms predominantly have the movable accent on the base. In the formation of compound and complex sentences it does not significantly depart from standard Slovene.
Keywords: Slovene; slovenščina; Slovene dialects; slovenska narečja; dialectology; dialektologija; Sveta Trojica; Slovenske gorice